1996
DOI: 10.1108/01443589610124390
|View full text |Cite
|
Sign up to set email alerts
|

The market valuation of wheat quality characteristics

Abstract: The views expressed are those of the authors and do not necessarily represent the policies of the US Department of Agriculture or the views of other US Department of Agriculture staff members. The authors would like to thank the anonymous referee for helpful suggestions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…There have been a number of applications for understanding quality characteristics of agricultural commodities (Larue and Lapan, 1990;Prescott and Puttock, 1990;Uri and Hyberg, 1996;Smith, 2000). The empirical application of characteristics of goods is represented by a hedonic price function where commodity price is a function of the good and its quality characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…There have been a number of applications for understanding quality characteristics of agricultural commodities (Larue and Lapan, 1990;Prescott and Puttock, 1990;Uri and Hyberg, 1996;Smith, 2000). The empirical application of characteristics of goods is represented by a hedonic price function where commodity price is a function of the good and its quality characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies on the impact that wheat quality has on prices use hedonic (pricing) models to test the effects of quality characteristics on annual domestic or international prices (Bale & Ryan, 1977;Espinosa & Goodwin, 1991;Larue, 1991;Parcell & Stiegert, 2003;Uri & Hyberg, 1996). Bale and Ryan (1977) analyze the impact of the protein content on the price ratio between various wheat classes, and find a mainly significant positive impact.…”
Section: Model Specification and Datamentioning
confidence: 99%
“…8 Uri and Hyberg (1996) employ shipment data of U. S. wheat exports to examine grain quality factors. Although a number of factors appear to be significant, market traders do not use many of these measures.…”
Section: Model Specification and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Fidan (2004) found that among the quality characteristics, the hectolitre weight and vitreousness were the major factors determining the price of durum wheat in the wheat market of Turkey, whereas (Karaman et al 2009) found that the hectolitre weight and the sedimentation values were the major determinants of the price of bread wheat. Although the results of studies on this subject in the international literature differ, the protein content seems to be the common and most important characteristic quality in the determination of wheat prices (Veeman 1987;Mercier 1993;Uri and Hyberg 1996). Larue (1991) showed that the marginal implicit value of protein varied depending on the wheat classification and in time.…”
mentioning
confidence: 99%